Karakter Tokoh Gatutkaca Dan Dadung Awuk Dalam Wayang Sebagai Pijakan Penciptaan Tari Gatutkaca Dadung Awuk Gaya Mangkunegaran - Aminudin; Kuncoro, Bimo; Wijayanto, R. Danang Cahyo (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
Gatutkaca Dadung Awuk Dance at Pura Mangkunegaran is a dance work created during the era of Mangkunegaran IV with its creator NN. In its development, this dance was reconstructed by (the late) Rono Suripto in the 1990s as an appreciation of special dance in Mangkunegaran and often used in welcoming guests. The main objective of this study is to examine the character of Gatutkaca and Dadung Awuk in wayang as a basis for the creation of the Gatutkaca Dadung Awuk Dance Mangkunegaran Style. The method used to analyse this artwork is the Hawkins method of creating artwork; namely: exploration, improvisation, and formation or composition. The Gathutkaca figure became an idol because of the personality inherent in him. Gatutkaca is the son of Werkudara (father) and Arimbi (mother). Gatutkaca is a knight and is the king of the Pringgandani kingdom who has a gagah anteb (dashing) character. One lakon of wayang performances entitled Parta Krama tells about the marriage of Arjuna (his uncle). Gatutkaca is asked to look for a dowry and he met Dadung Awuk. Dadung Awuk is a giant with the characteristics of rongeh, glece, brayak, and cakrak. In this meeting, a war occurred because the dowry for Arjuna’s marriage was guarded by Dadung Awuk, namely Kerbau Pancal Panggung (White lower legs). A creative idea emerged because of the meeting in Pura Mangkunegaran, that is a work of the Gatutkaca Dadung Awuk Dance.